2019
DOI: 10.1111/ijn.12720
|View full text |Cite
|
Sign up to set email alerts
|

High nursing workload is a main associated factor of poor hand hygiene adherence in Beijing, China: An observational study

Abstract: Aim The aim of the study was to explore the impact of nurse workloads on adherence to hand hygiene. Background Adherence to hand hygiene and nursing workloads have been linked to quality of patient care. Therefore, it was important to understand the relationship to safe patient care. Design This cross‐sectional study was performed from January 2016 to June 2016. Methods Workloads and adherence to hand hygiene for nurses on 3‐day shifts in a tertiary hospital were investigated in 2016. Actual hours worked per s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 52 publications
5
24
0
Order By: Relevance
“…Workload and burnout act as negative mediators of safe care [68,69]. A work environment characterised by a heavy workload and mental pressure [23,24,70] and frequent disruptions [71] has been implicated in reducing nurses' adherence to safety-related principles. There is an association between patient safety and the nurses' work environment [39,72,73] and implementation of patient-safety principles to prevent errors and adverse events [26,74].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Workload and burnout act as negative mediators of safe care [68,69]. A work environment characterised by a heavy workload and mental pressure [23,24,70] and frequent disruptions [71] has been implicated in reducing nurses' adherence to safety-related principles. There is an association between patient safety and the nurses' work environment [39,72,73] and implementation of patient-safety principles to prevent errors and adverse events [26,74].…”
Section: Discussionmentioning
confidence: 99%
“…Institutional systemic factors influencing nurses' adherence to and compliance with patient-safety principles are as follows: the organizational patient-safety climate [21], workload, time pressure, encouragement by leaders and colleagues [22][23][24], level of ward performance [25], provision of education for the improvement of knowledge and skills [11,18], institutional procedures or protocols, and also communication between healthcare staff and patients [11]. In addition, personal motivation, resistance to change, feelings of autonomy, attitude toward innovation, and empowerment are personal factors that impact on the nurses' adherence to patient-safety principles [26].…”
Section: Introductionmentioning
confidence: 99%
“…The indirect effect of workload on hand hygiene was also found to be signi cant in our study, which provides more explanation on how workload in uence hand hygiene compared to previous studies. For example, Ataiyero and Smith found that workload is one of the main barriers to hand hygiene, especially in developing countries based on narrative review and Theoretical Domains Framework [30,31], while Zhang found that high nursing workload is con rmed to be a main associated factor of poor hand hygiene in China [32]. Furthermore, the indirect effect of mental health on hand hygiene was also found to be signi cant in our study, while the direct effect was insigni cant, which was different from previous studies.…”
Section: Contributors Of Hand Hygiene Behaviormentioning
confidence: 99%
“…= 1.270, 1.400, 2.210, 1.634; P = 0.004, 0.001, 0.035, 0.003),which meant that control workload would increase the impact of medical professionals on CRPA. It confirmed that high nursing workload was a main associated factor of poor hand hygiene adherence which could lead to the spread of pathogens and aggravation of AMR [31]. Excessive workload may make medical professionals neglect the implementation of monitoring, guiding, rational use of antimicrobials and infection control measures, which can greatly increase the spread of drugresistant organism.…”
Section: Discussionmentioning
confidence: 88%